Top-down enrichment of oil-degrading microbial consortia reveals functional streamlining and novel degraders - Wu, Huijun; Du, Xianyuan; Zheng, Jin; Li, Xingchun; Song, Quanwei; Yan, Yuhao; Ma, Anzhou; Xu, Anming; Li, Jufeng (Frontiers in Microbiology, 2025)
IntroductionTop-down microbial enrichment is a reliable approach for understanding and designing microbiomes for crude oil remediation. Environmental variables serve as valuable determinants for selecting desired microbiomes with superior performance. However, the linkages between selection methods and the structure and function of desired microbiomes remain unclear.MethodsThis study integrated substrate concentration gradients and cultivation patterns to investigate how selection pressures shape top-down enriched crude oil-degrading consortia. The resulting communities were analyzed using 16S rRNA gene sequencing, metagenomics, and co-occurrence network analysis. Key bacterial strains were isolated to validate their individual degradation capabilities.ResultsThe top-down process led to a significant reduction in phylogenetic diversity but a notable increase in the potential for xenobiotic degradation and metabolic. The final consortia, GT4, achieved a 55.72% degradation rate of crude oil at an initial concentration of 5 g/L within 7 days. Metagenomic analysis identified Microbacterium as dominant genus harboring key enzymes for the degradation of alkanes and aromatic compounds. Co-occurrence network analysis revealed Mesorhizobium as a keystone genus, showing positive associations with multiple diazotrophic bacteria and hydrocarbon degrading bacteria. Nine bacterial strains were isolated from the consortium. Among them, Microbacterium sp. WS3 and Cellulosimicrobium sp. WS9 exhibited high degradation efficiencies (57.85 and 58.60%, respectively). To the best of our knowledge, this study provides the first experimental evidence for crude oil degradation by Paracandidimonas and Caulobacter, with degradation rates of 51.19 and 40.90%, respectively.DiscussionThese findings highlight the effectiveness of top-down enrichment strategy in generating functionally streamlined consortia and uncover novel oil-degrading microbes with potential for bioremediation applications.